What is the Efficacy of Existing Interventions for Reducing the Impact of Post-Traumatic Osteoarthritis Following Anterior Cruciate Ligament Injury? A Systematic Review - McIntosh, Catherine (Auckland University of Technology, 2022)
Introduction. Anterior Cruciate Ligament (ACL) injury has been identified as a risk factor for developing post-traumatic osteoarthritis (PTOA). The individual and societal burden of ACL injuries and PTOA are considerable in Aotearoa New Zealand (AoNZ). This burden is predicted to increase if there is no change in how these injuries are managed. A variety of ACL injury management options exist in AoNZ. Rehabilitation is a recognized component of ACL injury management. The efficacy of different ACL rehabilitation interventions on reducing the impact of PTOA is unknown. Objective. This systematic review aimed to identify, synthesise and critique the findings of research that has evaluated the effectiveness of ACL injury management on the development of PTOA. This review will appraise the quality of the identified literature, to answer the research question, what is the efficacy of existing interventions for reducing the impact of PTOA following ACL injury? Methods. A systematic search of electronic databases CINAHL, SPORTDiscus MEDLINE (via EBSCO) and Scopus was completed and studies relevant to the objective were identified. A quality critique of the selected studies was undertaken using a modified Downs and Black appraisal tool. Data central to the study objective were extracted and analysed. Results. Six articles were retained for final review, quantified as good quality. Five studies compared the effect of surgical anterior cruciate ligament repair (ACLR) with non-surgical management of ACL injuries on the development of PTOA. Only one study investigated the effect of different ACL rehabilitation protocols on the development of PTOA. The incidence of PTOA following ACL injury was comparable regardless of the management interventions compared in each of the studies. Conclusion. Current research shows the risk of PTOA after ACL injury is not changed by ACL injury management. Further research is required to inform ACL injury management to reduce the long-term impact of ACL injury and optimise the wellbeing of the growing ACL-injured population. In the meantime, the evidence supports physiotherapists to implement programmes for ACL injury prevention and promoting knee joint health following ACL injury.